Professor Nimio de Anquín. Analysis of his political thought and his career at the University of Córdoba (Argentina) - Vera de Flachs, Maria Cristina; Sillau Pérez, Antonio (Sociedad de Historia de la Educación Latinoamericana y la Universidad Pedagógica y Tecnológica de Colombia, 2021)
Objective: this paper analyzes the political ideas of Professor Nimio de Anquín related to his academic and political career at the University of Córdoba. The temporal space of the work is framed especially between 1930 and 1943, a period of definitive break of the consensus that existed around the nineteenth-century liberal project of modern Argentina and the growing proliferation, from the extreme right, of an illiberal nationalism of which Professor de Anquín was one of its visible representatives in the interior of the country, in its Catholic side. Originality/support: We consider this research relevant because it penetrates into the biography of a character, whose influence lasted until the 1970s, focusing on his political ideas and his condition as an active member of the university community of Córdoba. Method: the work of this research is biographical. The reconstruction of the biographical aspects of Nimio de Anquín studied in this work and in relation to the context in which he acted, has been possible through the consultation of public and private documentary repositories that allowed the access to published and unpublished sources, as well as personal interviews. Strategy/ information gathering: The strategies followed included the search and organization of documents from the General and Historical Archive of the National University of Córdoba, the Historical Archive of the Province of Córdoba, the Museum of the Reform and the private archive of Dr. Alberto Caturelli. Conclusions: this work allows us to broaden the analysis of the political ideas of those who confronted the university reformism and their presence in university politics.